Acute neonatal and benign citrullinaemia in one sibship. Issue 2 (February 1978) - Burgess, E A; Oberholzer, V G; Semmens, J M; Stern, J
Abstract : Citrullinaemia was diagnosed in an infant who died at age 8 days. The clinical picture was of the disease in its acute neonatal form. A sib has a blood citrulline of 100 times normal and about 10% of normal argininosuccinic acid synthetase activity in cultured fibroblasts. Clinically he is normal with an IQ of 94 on the Wechsler Intelligence Scale for Children.